Rudyard Kipling’s Novel the Jungle Book as Moral Literacy Material on EFL Learning - Mutiarani Mutiarani; Hasanul Misbah; Aliya Nafisa Karyadi (English Language in Focus (ELIF), 2020)
Education plays an important role in the formation of human character. One of the keys to successful students who have a strong personality is the selection of learning material. This study aims to explain that moral literacy in the novel The Jungle Book by Rudyard Kipling in the form of ethical sensitivity, ethical reasoning abilities, and moral imagination. This research is a qualitative descriptive type and uses an objective approach. The theory used is Nancy Tuana's Moral Literacy. The results showed that the form of ethical sensitivity in The Jungle Book is in the brotherhood and heroic action The form of ethical reasoning is in the reasoning for the nature of gratitude and the nature of the consequences of revenge. Moral imagination lies in brotherhood and self-defense efforts. Thus, moral literacy in the novel can be an alternative material for moral literacy the which is useful in the development of students' character.